Strategies to Increase Students' Registering Interest in Private Schools - Anisa Maulidya; Miftah Royyani (Transformasi Manageria: Journal of Islamic Education Management, 2023)
Private schools are schools founded by religious and non-religious organizations. The contribution of private schools to the nation and state is enormous. However, one of the problems faced by private schools is the lack of students’ registering interest. this paper aims to find out the strategy to increase students' registering interest in private schools. There are several strategies that can be carried out by private institutions to increase the interest of applicants, namely: 1) good branding management; 2) having a reliable marketing strategy; 3) improving school quality; and 4) providing discounts. Keyword: Private Schools, Students' Registering, Increase Students' Registering